Management of Atypical Squamous Cell Cases: A Prospective Study of Women seen at a Private Health Service in Northeastern Brazil - Oliveira, Geilson Gomes de; Oliveira, Judite Maria da Silva Costa de; Eleutério, Renata Mirian Nunes; Eleutério Júnior, José (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To assess the management chosen by gynecologists after atypical squamous cells (ASCs) cytology results, and to evaluate the outcomes of these cases in Brazilian women.Methods A prospective observational study evaluated the initial management offered by the gynecologist in the case of 2,458 ASCs cytology results collected between January of 2010 and July of 2016. The outcomes of the cytology, high-risk human papilloma virus (HR-HPV) test and histology were compared in two subgroups: atypical squamous cells of undetermined significance (ASC-US) and atypical squamous cells-cannot exclude high-grade squamous intraepithelial lesion (ASC-H).Results In many cases of ASC-US (36.97%) and ASC-H (40.50%), no clinical actions were taken. Cytology was the most frequent follow-up chosen, including for cases of ASC-H, which goes against the conduct recommended in the national guideline. In women over 30 years of age, the period of time elapsed between an ASC-US result and a new cytology was in 13.03 months, in disagreement with the national guideline recommendations (p < 0.0001). Negative for intraepithelial lesions or malignancy (NILM) cytologic (p = 0.0026) and histologic (p = 0.0017) results in the follow-up were associated with prior ASC-US, while negative results for ASC-H were cytologically (p < 0.0001) and histologically associated with high-grade squamous intraepithelial lesion (HSIL) (p < 0.0001). Two invasive cervical carcinomas (ICCs) were found in the follow-up for ASC-H, and there was a statistically significant association (p = 0.0341). A positive HR-HPV test was associated with ASC-H (p = 0.0075).Conclusion The data suggest that even for a population of Brazilian women assisted at private clinics, the national guidelines recommendations for ASCs results are not followed.
Keywords: uterine cervical neoplasm; disease management; atypical squamous cells of the cervix; papanicolaou test; human papillomavirus